Metallothionein 3 Inhibits 3T3-L1 Adipocyte Differentiation via Reduction of Reactive Oxygen Species - Yuankuan Li; Sung Ho Lee; Meiyu Piao; Hyung Sik Kim; Kwang Youl Lee (MDPI AG, 2023)
Metallothionein 3 (MT3), also known as a neuronal growth-inhibitory factor, is a member of the metallothionein family and is involved in a variety of biological functions, including protection against metal toxicity and reactive oxygen species (ROS). However, less is known about the role of MT3 in the differentiation of 3T3-L1 cells into adipocytes. In this study, we observed that MT3 levels were downregulated during 3T3-L1 adipocyte differentiation. Mt3 overexpression inhibited adipocyte differentiation and reduced the levels of the adipogenic transcription factors C/EBPα and PPARγ. Further analyses showed that MT3 also suppressed the transcriptional activity of PPARγ, and this effect was not mediated by a direct interaction between MT3 with PPARγ. In addition, Mt3 overexpression resulted in a decrease in ROS levels during early adipocyte differentiation, while treatment with antimycin A, which induces ROS generation, restored the ROS levels. Mt3 knockdown, on the other hand, elevated ROS levels, which were suppressed upon treatment with the antioxidant N-acetylcysteine. Our findings indicate a previously unknown role of MT3 in the differentiation of 3T3-L1 cells into adipocytes and provide a potential novel target that might facilitate obesity treatment.